STRATEGI BRAIN BASED LEARNING DALAM PENGAJARAN BAHASA JEPANG DI MAN MOJOKERTO - Yulia Pratitis Yusuf (Universitas Negeri Surabaya, 2017)
Japanese language teaching by lecture method used is irrelevant. It can be seen from the output of students who graduate high school, they generally have not been able to use the Japanese language in the context of natural communication. Japanese language learning should be done in harmony with the way the brain to learn something. It was due to the close links between the brain and language acquisition. Caine said there are twelve principles of brain work is the basis for the implementation of brain-based teaching. The twelve principles of brain functions must be implemented in three stages, namely the stage of teaching Japanese language to understand ã€Œã‚ã‹ã‚‹ã€, remembering ã€ŒãŠã¼ãˆã‚‹ã€and use ã€Œã¤ã‹ã†ã€. With Brain Based Learning troughout the students potential can be optimally stimulated to learn Japanese. And when the twelve principles of brain functions in learning something can be understood by Japanese teachers well, then learning Japanese would be effective, enjoyable, meaningful and the most importantly, both Brains hemispheres students can alsao develop optimally.